Functional Disability in Late‐Middle‐Aged and Older Adults Admitted to a Safety‐Net Hospital. Issue 11 (3rd November 2014) - Brown, Rebecca T.; Pierluissi, Edgar; Guzman, David; Kessell, Eric R.; Elizabeth Goldman, L.; Sarkar, Urmimala; Schneidermann, Michelle; Critchfield, Jeffrey M.; Kushel, Margot B.
<x xml:space="preserve">Abstract</x> Objectives To determine the prevalence of preadmission functional disability in late‐middle‐aged and older safety‐net inpatients and to identify characteristics associated with functional disability by age. Design Cross‐sectional analysis. Setting Safety‐net hospital in San Francisco, California. Participants English‐, Spanish‐, and Chinese‐speaking community‐dwelling individuals aged 55 and older admitted to a safety‐net hospital with anticipated return to the community (N = 699). Measurements At hospital admission, participants reported their need for help performing five activities of daily living (ADLs) and seven instrumental activities of daily living (IADLs) 2 weeks before admission. ADL disability was defined as needing help performing one or more ADLs and IADL disability as needing help performing two or more IADLs. Participant characteristics were assessed, including sociodemographic characteristics, health status, health‐related behaviors, and health‐seeking behaviors. Results Overall, 28.3% of participants reported that they had an ADL disability 2 weeks before admission, and 40.4% reported an IADL disability. The prevalence of preadmission ADL disability was 28.9% of those aged 55 to 59, 20.7% of those aged 60 to 69, and 41.2% of those aged 70 and older (P < .001). The prevalence of IADL disability had a similar distribution. The characteristics associated with functional disability differed according to age; in participants aged 55 to 59, African Americans had a higher odds of ADL and IADL disability, whereas in participants aged 60 to 69 and aged 70 and older, inadequate health literacy was associated with functional disability. Conclusion Preadmission functional disability is common in individuals aged 55 and older admitted to a safety‐net hospital. Late‐middle‐aged individuals admitted to safety‐net hospitals may benefit from models of acute care currently used for older adults that prevent adverse outcomes associated with functional disability.